A Study of Accuracy and Translation Technique in Narrative Text by Using Google Translate Application - Hasibuan, Zainuddin (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2025)
This study aims to determine the accuracy of narrative text translation by using Google Translate Application and to describe translation techniques which are used by the translator in translating source text (ST) into target Text (TT). This research is a qualitative method that uses descriptive research approach to analyze the accuracy of narrative text translation and translation techniques. The result show The proportion of narrative text translated using the Google Translate application, namely from 16 analyzed data, resulting in 9 data (56.25%) as an accurate translation, 5 data (31.25%) as a less accurate translation, and 2 data (12.5%) as a not correct translation. It means that using the Google Translate Application can provide effective and accurate translations while also assisting us in transforming source language into target content fast and efficiently. Translation techniques which are used by the translator consists of single translation technique and couplet translation technique. Single translation technique consists of 14 data while couplet translation technique consists of 2 data. Literal translation technique consists of 6 data (37,5%), modulation translation technique consists of 3 data (18,75%), calque translation technique consists of 3 data (18,75%), modulation + calque and calque + modulation translation technique both of them consists of 1 data (6,25%), transposition translation technique consists of 1 data (6,25%), and reduction translation technique is also only 1 data (6,25%). The most dominant translation techniques which are used by the translator is literal translation that have 6 data (37,5%). It means that the form of translation adopting domestication of translation than a foreignizing translation.